Hutchinson Dictionary of Abbreviations - Helicon (Helicon Publishing, 2006)
Clear explanations of abbreviations from fields such as computing, current affairs, medicine, education, warfare, and even newspaper advertisements.
Keywords: Abbreviations, English; Acronyms; Electronic books. -- local